Experimental investigation of particle-induced pressure loss in solid–liquid lifting pipe - Song, Yue-wen; Zhu, Xiao-jun; Sun, Zhi-qiang; Tang, Da-sheng (Journal of Central South University, 2017)
In order to investigate the characteristics of particle-induced pressure loss in the solid–liquid lifting pipe, a series of experiments were conducted in 200 mm diameter lifting pipe. Simulation manganese nodules with five different mean diameters of 10 mm, 20 mm, 30 mm, 40 mm and 50 mm were used, both in isolation and a combination in equal fraction by mass. The flow velocities in the lifting pipe ranged from 0.12 m/s to 1.61 m/s, and the mass of particles employed was 10 kg for each particle diameter. Three regimes, wavy bed, partly fluidization, and fully fluidization, were observed over the flow velocity. The solid–liquid pressure drop data were measured by differential pressure transmitter, and pressure drop caused by the solid particles was calculated and analyzed. The results show that the evolutions of the pressure loss due to solid particles are relevant to the solid–liquid flow regimes, and they are distinctly influenced by fluid velocity and particle size.